Diversity of lichens of the genus Cladonia P. Browne (Cladoniaceae, Ascomycota) in the Karegodsky Nature Reserve (Tomsk Oblast, Western Siberia) - Daria I. Kazantseva; Alexander S. Revushkin; Aleksandr L. Ebel; Vera V. Koneva (Acta Biologica Sibirica, 2026)
An inventory study of lichens of the genus Cladonia P. Browne was conducted in the Karegodsky Zoological Nature Reserve, located within the Ob–Chulym interfluve (Molchanovsky District, Tomsk Oblast, Western Siberia). Field investigations were carried out in August 2025 using route methods covering the main plant communities and substrate types. Pine forests, willow–poplar forests, birch–aspen forests, and anthropogenically disturbed areas were surveyed. More than 350 specimens were collected and identified. A total of 45 Cladonia species were recorded in the study area, which is comparable to the 44 species documented for the entire Ob–Chulym interfluve and indicates high representativeness of the reserve's lichen biota. Twelve species are reported for the first time for this physiographic region, substantially expanding knowledge of Cladonia distribution in Western Siberia. The highest species richness was observed in pine forests, characterized by high light availability and substrate diversity. Substrate preference analysis revealed predominance of epixylic and epigeic forms, as well as a high proportion of eurysubstrate species, reflecting the ecological plasticity of Cladonia in taiga ecosystems. The presence of pollution-sensitive species indicates favorable ecological conditions in the reserve. These data provide a foundation for future monitoring of lichen flora and assessment of natural complex dynamics in protected areas.